Voltage-gated transient currents in bovine adrenal fasciculata cells. II. A-type K+ current (The Rockefeller University Press, 1993)
In whole cell patch clamp recordings on enzymatically dissociated adrenal zona fasciculata (AZF) cells, a rapidly inactivating A-type K+ current was observed in each of more than 150 cells. Activation of IA was steeply voltage dependent and could be described by a Boltzmann function raised to an integer power of 4, with a midpoint of -28.3 mV. Using the "limiting logarithmic potential sensitivity," the single channel gating charge was estimated to be 7.2 e. Voltage-dependent inactivation could also be described by a Boltzmann function with a midpoint of -58.7 mV and a slope factor of 5.92 mV. Gating kinetics of IA included both voltage-dependent and -independent transitions in pathways between closed, open, and inactivated states. IA activated with voltage-dependent sigmoidal kinetics that could be fit with an n4h formalism. The activation time constant, tau a, reached a voltage- independent minimum at potentials positive to 0 mV. IA currents inactivated with two time constants that were voltage independent at potentials ranging from -30 to +45 mV. At +20 mV, tau i(fast) and tau i(slow) were 13.16 +/- 0.64 and 62.26 +/- 5.35 ms (n = 34), respectively. In some cells, IA inactivation kinetics slowed dramatically after many minutes of whole cell recording. Once activated by depolarization, IA channels returned to the closed state along pathways with two voltage-dependent time constants which were 0.208 s, tau rec-f and 10.02 s, tau rec-s at -80 mV. Approximately 90% of IA current recovered with slow kinetics at potentials between -60 and -100 mV. IA was blocked by 4-aminopyridine (IC50 = 629 microM) through a mechanism that was strongly promoted by channel activation. Divalent and trivalent cations including Ni2+ and La3+ also blocked IA with IC50's of 467 and 26.4 microM, respectively. With respect to biophysical properties and pharmacology, IA in AZF cells resembles to some extent transient K+ currents in neurons and muscle, where they function to regulate action potential frequency and duration. The function of this prominent current in steroid hormone secretion by endocrine cells that may not generate action potentials is not yet clear.